Multilevel Converters: Analysis, Modulation, Topologies, and Applications - Grandi, Gabriele (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book is a collection of scientific papers concerning multilevel inverters examined from different points of view. Many applications are considered, such as renewable energy interface, power conditioning systems, electric drives, and chargers for electric vehicles. Different topologies have been examined in both new configurations and well-established structures, introducing novel and particular modulation strategies, and examining the effect of modulation techniques on voltage and current harmonics and the total harmonic distortion.